Clinical outcomes of endoscopic resection for superficial non-ampullary duodenal tumors - Kuroki, Kazutaka; Sanomura, Yoji; Oka, Shiro; Yorita, Naoki; Kurihara, Mio; Mizumoto, Takeshi; Yoshifuku, Yoshikazu; Arihiro, Koji; Tanaka, Shinji; Chayama, Kazuaki (Endoscopy International Open, 2020)
Background and study aims Because superficial non-ampullary duodenal epithelial tumors (SNADETs) are relatively rare, studies evaluating the outcomes of endoscopic resection (ER) for SNADETs are limited. Therefore, this study aimed to evaluate the clinical validity of ER for SNADETs.Patients and methods The study participants included 163 consecutive patients (108 men; mean age, 61.5 ± 11.3 years) with 171 SNADETs, excluding patients with familial adenomatous polyposis resected by ER, at Hiroshima University Hospital between May 2005 and September 2016. Clinicopathological features and the outcomes of ER for 171 cases were retrospectively analyzed. Additionally, the prognosis of 135 patients with more than 12 months’ follow-up was analyzed.Results Mean diameter of SNADETs was 10.7 ± 7.2 mm. Most of the SNADET cases were classified as category 3 (71 %, 121/171), but some were category 5 (2 %, 3/171). En bloc resection rates were 93 % (146/157), 100 % (7/7), and 86 % (6/7) in endoscopic mucosal resection (EMR), polypectomy, and in endoscopic submucosal dissection (ESD) cases, respectively. Complete resection rates were 90 % (141/157), 100 % (7/7), and 71 % (5/7) in EMR, polypectomy, and ESD cases, respectively. Emergency surgery was performed in two patients with intraoperative perforation and in two with delayed perforation without artificial ulcer bed closure after ER. Since endoscopic closure of ulcer by clipping was performed, delayed perforation has not occurred. Local recurrence occurred in 1.2 %, but no metastasis to lymph nodes or other organs occurred after ER. No patient died of primary SNADETs.Conclusion Our data supported the clinical validity of ER for SNADETs. However, delayed perforation should be given much attention.